2022
DOI: 10.1007/s11845-021-02910-x
|View full text |Cite
|
Sign up to set email alerts
|

The symptomatic breast services in a university hospital: pandemic peak compared to the pre-pandemic year and future implications

Abstract: Background COVID-19 infection led to a substantial overhaul of the symptomatic breast services within the UK. Aim The purpose of this study was to evaluate the pattern of primary care referrals to the symptomatic one-stop clinic during the pandemic. This study also provides a snapshot of the workings of symptomatic breast services and the scope for improvements. Methods The data points were collected for 1 month during the peak of the pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 6 publications
(6 reference statements)
1
10
0
Order By: Relevance
“…The referral rate fall is linked to several factors, including the GPs more stringent referral approach, health facility avoidance by patients prone to nosocomial infection, and government and media campaign against hospital visits. Our study shows an increased 2ww target and cancer diagnosis rate in the pandemic era, similar to previous findings [ 15 , 16 ]. The increased 2ww target is partly due to the diversion of facilities and clinicians to the one-stop clinic following the suspension of benign and reconstructive procedures and family history clinics.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The referral rate fall is linked to several factors, including the GPs more stringent referral approach, health facility avoidance by patients prone to nosocomial infection, and government and media campaign against hospital visits. Our study shows an increased 2ww target and cancer diagnosis rate in the pandemic era, similar to previous findings [ 15 , 16 ]. The increased 2ww target is partly due to the diversion of facilities and clinicians to the one-stop clinic following the suspension of benign and reconstructive procedures and family history clinics.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, the 2ww referrals reduced by 28.3% in 2020 compared with those in 2019. Other studies have recorded fewer urgent and symptomatic referrals during the pandemic [ 15 - 18 ]. We note that there is no difference in the referral rates of patients aged younger and older than 50 years, in contrast to the finding of Bansal et al [ 15 ], which showed reduced referral rates in patients aged more than 50 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An initial 2451 citations were identified for title and abstract screening, of which 77 were eligible for inclusion ( Fig. 1 ) [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] ,…”
Section: Resultsmentioning
confidence: 99%
“…For 3 studies with multiple publications reporting different or complementary outcomes, we selected the most recently published for inclusion [ 34 , 57 , 59 ], and extracted relevant data (where available) from the other superseded publications [ [85] , [86] , [87] ] but did not include them as separate papers. Therefore, a total of 74 studies were included in this review [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , ...…”
Section: Resultsmentioning
confidence: 99%